Keanekaragaman Jenis Artocarpus di Bantaran Sungai Desa Beringin Kecana Kecamatan Tabunganen Kalimantan Selatan - Rida Sita Dewi; Hardiansyah Hardiansyah; Mahrudin Mahrudin (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
The genus Artocarpus has tree habitus characteristics, and has stem characteristics that produce a special liquid (sap) with a stem growth type, namely monoceus with unisexual flowers. Artocarpus is a type of tropical fruit plant that is multi-functional and can be grown in tropical areas with an altitude of less than 1000 meters above sea level. The purpose of the study was to describe the diversity of Artocarpus species on the riverbanks of Beringin Kencana Village, Tabunganen District. This research method uses a descriptive approach. The results of the species diversity data were analyzed descriptively. The results showed that on the riverbanks of Beringin Kencana Village, Tabunganen Subdistrict, 4 types of Artocarpus were found, namely: 1) Jackfruit (Artocarpus heterophyllus Lamk.), Bilulang Jackfruit (Artocarpus heterophyllus Lamk.), Jackfruit Porridge (Artocarpus heterophyllus Lamk.) which belongs to one variety, while Sukun (Artocarpus altilis (Park.) Fosberg.), Cempedak (Artocarpus integer (Thunb.) Merr.), and Keledang (Artocarpus lanceifolius Roxb.) are other species.